Assessing cybersecurity awareness and security practices among university students in Jordan - Khader Musbah Ismail Titi (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
This paper sets out to evaluate the degree to which Jordanian university students genuinely comprehend and apply cybersecurity principles in their everyday digital lives. The rationale for undertaking this investigation is compelling: as cyber threats continue to intensify and diversify, remarkably little granular evidence exists to identify which sub-populations within the Jordanian student body are most vulnerable due to knowledge gaps. A structured survey reaching 150 students recruited from a range of academic departments served as the empirical foundation, with all quantitative analyses conducted using SPSS and MS-Excel. The analysis examined three demographic dimensions: gender, academic discipline, and geographic origin (urban versus rural). Students enrolled in computing and information technology programmes consistently demonstrated superior preparedness relative to their peers, and urban-based students exhibited more robust awareness profiles than those from rural areas. Building on these findings, the paper makes a case for systematic awareness programmes and for embedding cybersecurity content into curricula across all disciplines rather than restricting it to technical fields.